Clinicopathological Features and Prognoses of Patients With Splenic Metastases From Breast Cancer: A Single-Centre, Retrospective Study - Xiaofeng Xie MD; Mingrui Ma MD; Xue Bai BS; Jing Hu MD; Haijie Zheng MD; Xiongqi Guo BS; Jiayi Huang MD; Xuelian Chen PhD; Liping Chen BS; Xiaofeng Lan BS; Lin Song BS; Caiwen Du PhD (Cancer Control)
Purpose Splenic metastases (SM) from breast cancer (SMBC) are exceedingly rare. To date, the relevant literature is primarily based on pan-tumour species, with only a few studies exploring SM specifically in relation to breast cancer. As such, the present retrospective study explored the clinicopathological characteristics and prognoses of patients with SMBC at the breast care centre of the authors’ hospital. Methods Data from patients newly diagnosed with metastatic breast cancer (MBC) between June 2017 and June 2022 were extracted from medical records at the authors’ hospital. Clinicopathological characteristics and their associations with progression-free survival (PFS [time from diagnosis of initial recurrence and/or metastasis to diagnosis of SM]), first overall survival ( 1st OS [time from diagnosis of breast cancer to death or last follow-up visit]), and second overall survival ( 2nd OS [time from diagnosis of SM to death or last follow-up visit]) were analysed in patients with SMBC. Results In total, 1009 patients with MBC were identified, of whom 18 (1.7%) had SM. T1 and T2 stages were documented in 15 (83.3%) patients, whereas N2 and N3 were documented in 13 (62.2%). 14 (77.8%) patients were oestrogen receptor and/or progesterone receptor positive. A Ki-67 index ≥ 30% accounted for 72.2% (13/18) of cases, and all patients were histological grade II or III. Liver and/or lung metastases were documented in all 18 (100%) patients. Median PFS was 6.3 months. The median 1st OS and 2nd OS were 41.8 and 10.6 months, respectively. The number of previous treatment lines before diagnosis of SM was a significant adverse prognostic factor for PFS, and disease-free survival was a significant adverse prognostic factor for 1st OS. Conclusion SMBC commonly presents with diffuse multiple organ metastases in the terminal stage of malignancy and has a poor prognosis, which may provide deeper insight into SMBC for clinicians.